2017
DOI: 10.1111/cen.13333
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of dietary approaches to stop hypertension diet on weight loss, anti‐Müllerian hormone and metabolic profiles in women with polycystic ovary syndrome: A randomized clinical trial

Abstract: Adherence to the DASH diet for 12 weeks among PCOS women had beneficial effects on BMI, AMH, insulin metabolism, SHBG, FAI, NO and MDA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 35 publications
4
67
1
14
Order By: Relevance
“…In addition, following the DASH diet was associated with an improvement in sex hormone levels. 45 Similar results were obtained by Asemi et al 46 In a group of 48 women with PCOS, following the DASH diet was associated with a significant reduction in insulin levels and HOMA-IR index values compared to a diet with the same distribution of macroelements, but obtained from other food sources. For 8 weeks, the subjects in both the study group and the control group followed diets which provided 18% of E from protein, 52% from carbohydrates and 30% from fats.…”
Section: Diets Used In Irsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, following the DASH diet was associated with an improvement in sex hormone levels. 45 Similar results were obtained by Asemi et al 46 In a group of 48 women with PCOS, following the DASH diet was associated with a significant reduction in insulin levels and HOMA-IR index values compared to a diet with the same distribution of macroelements, but obtained from other food sources. For 8 weeks, the subjects in both the study group and the control group followed diets which provided 18% of E from protein, 52% from carbohydrates and 30% from fats.…”
Section: Diets Used In Irsupporting
confidence: 80%
“…Many researchers have found that diets with modified levels of particular FA, low-glycemic-index diets, the Dietary Approaches to Stop Hypertension (DASH diet), and the Mediterranean diet have positive effects. [42][43][44][45][46][47][48][49][50][51][52] The relationship between IR and the Mediterranean diet, the DASH diet and a vegetarian diet An analysis of the data obtained from the patients of the Third National Health and Nutrition Examination Survey (NHANES III) showed that scores indicating the similarity of the respondents' diet to the Mediterranean diet were associated with lower BMI and waist circumference. Lower waist circumference correlated with lower glycated hemoglobin levels, fasting insulin levels and HOMA-IR index values.…”
Section: Diets Used In Irmentioning
confidence: 99%
“…4,5 Other studies with similar presentation include Foroozanfard et al and subrata et al where the primary and secondary infertility was 69% and 31%, 73% and 27% respectively. 2,3 Contrary to our study, in a study conducted by Eleje et al, majority were presented with secondary infertility (76.5%) and only 23.5% being primary infertility. 6 This may be due to geographical variation related to a particular area where STI's and pelvic inflammatory diseases are more prevalent and also early marriages are more common (Table 2).…”
Section: Discussioncontrasting
confidence: 93%
“…Программы контроля веса, предлагаемые больным СПЯ, часто направлены на ограничение калорий и увеличение физической активности. В результате модификации образа жизни и потере веса всего на 5-10% от первоначальной массы имеют положительную динамику многие клинические и лабораторные показатели [11]: уменьшается интенсивность гиперандрогении [12], становится менее выражена резистентность к инсулину [12], уменьшаются уровни атерогенных фракций липидов [13], становится более регулярным менструальный цикл [11], появляются спонтанные овуляторные менструальные циклы и увеличивается процент наступления беременности [14,15] и улучшаются показатели психологического статуса [11,68]. Кроме того, высокие уровни андрогенов у женщин с СПЯ обусловливают большую тягу к жирным и углеводистым продуктам, что дополнительно препятствует снижению веса.…”
unclassified
“…Для повышения сытости на фоне низкокалорийной диеты рекомендуют увеличить потребление белка, но высокобелковая диета не приводят к более высокой потере веса или более значительному улучшению метаболических симптомов по сравнению с низкобелковыми диетами [16]. По данным недавнего исследования диета для пациентов с гипертензией (включающая фрукты, овощи, цельные зерна, молочные продукты с пониженным содержанием жира, холестерина) приводит к сопоставимой потере веса при сравнении со стандартной низкокалорийной диетой у женщин с СПЯ и значительным улучшениям чувствительности к инсулину, показателям глобулина, связывающего половые гормоны, и антимюллерова гормона [12]. Учитывая, что больные СПЯ находятся в группе риска расстройства поведения и беспорядочного питания, важно включать в алгоритм ведения консультацию психоневролога.…”
unclassified